The Language Game of Goodness - Nørreklit, Lennart (Journal of Pragmatic Constructivism, 2021)
In a performance culture, the individual who manages to be the best, is glorified. The rest become marginalised or even excluded from the community. The right to define what is the best is often in the hands of few, and most often these criteria have roots in a form of emotivism. The criteria are thereby weakly defined, and bendable in favour of those who seem to have taken control. In response to the aim of being the best, Lennart Nørreklit develops a conceptual framework for being good, the language game of goodness. A society based on goodness, and the ethics of being good are inclusive because being good is simultaneously possible for a community of people. The paper contributes with a highly critical discussion of the performance society, and it provides an alternative for organising societies.